THE RELEVANCY BETWEEN LEARNING MATERIALS AND METHODS IN ENTREPRENEURSHIP LEARNING PROCESS IN HIGHER EDUCATION - Sulastri Sulastri; Zakaria Wahab; Vieronica Varbi Sununianti (Faculty of Economics and Business Udayana University, 2017)
THE RELEVANCY BETWEEN LEARNING MATERIALS AND METHODS IN ENTREPRENEURSHIP LEARNING PROCESS IN HIGHER EDUCATION. Sulastri Management, Faculty of Economics, UniversitasSriwijaya ZakariaWahab Management, Faculty of Economics, UniversitasSriwijaya VieronicaVarbiSununianti, S.Sos, M.Si Sociology, Faculty of Social Sciences and Politics, UniverstiasSriwijaya ABSTRACT Entrepreneurship program has become a national policy that is believed to be a tool to reduce unemployment and poverty. Therefore, entrepreneurship has become a national curriculum in almost every study program and has incorporated entrepreneurship module as one of the subjects in achieving learning outcome and graduate profile. The terms in entrepreneurship are also growing, with the aim of establishing a social construction towards the understanding of entrepreneurship as a science, which contains elements of knowledge, skills and attitudes. Besides, entrepreneurship construct that need to be built in the learning process is very complex and involves multiple disciplines, so it is important to study empirically the relevancy between learning materials and methods in entrepreneurship learning process in higher education. This study aims to examine whether there are differences in the learning materials and methods in entrepreneurial learning at higher education level. The research is carried out in several public and private universities with a sample of 304 students from some courses both for the field of sciences and social studies that have entrepreneurship as one of their taught modules. It can be concluded that entrepreneurial learning materials can be grouped in the aspect of (1) knowledge; (2) skills and (3) attitude. In each aspect, the learning materials are collected and grouped and observed on itslearning methodology. The results by using Anova testing show that there are differences in some teaching materials and learning methods in the same faculty or inter- faculty at several universities. Furthermore, in the cognitive construction of the entrepreneurship metaphor (innovation, creative, proactive and risk -taking), it is found that it has not been delivered usingrelevant learning methods, as well as learning models of personal development. Keywords : Teaching materials , Methods of learning , Entrepreneurship Relevansi Materi dan Metode Dalam Proses Pembelajaran Kewirausahaan PadaTingkat Pendidikan Tinggi Sulastri Program StudiManajemenFakultasEkonomiUniversitasSriwijaya Email : sulastri2310@gmail.com ZakariaWahab Program StudiManajemenFakultasEkonomiUniversitasSriwijaya & VieronicaVarbiSununianti, S.Sos, M.Si JurusanSosiologi, FISIP, UniversitasSriwijaya RINGKASAN Program kewirausahaan telah menjadi kebijakan nasional yang diyakini sebagai alat untuk mengurangi tingkat pengangguran dan kemiskinan. Implikasinya, kewirausahaan telah menjadi kurikulum nasional di hampir disetiap program studi dan telah memasukkan mata kewirausahaan sebagai salah satu mata kuliah untuk mencapai tujuan learning ooutcome dan profil lulusan. Istilah-istilah kewirausahan juga semakin berkembang, dengan tujuan untuk membangun konstruksi sosial terhadap pemahaman kewirausahaan sebagai suatu ilmu yang mengandung unsur pengetahuan, keterampilan dan sikap. Disamping itu konstruk kewirausaahan yang akan dibangun dalam proses pembelajaran sangat kompleks dan melibatkan beberapa disiplin ilmu, sehingga penting untuk diteliti secara empirik bagaimana RelevansiMateridanMetodePembelajaranKewirausahaanPada Tingkat Pendidikan Tinggi. Penelitian ini bertujuan untuk menguji apakah terdapat perbedaan materi dan metode dalam pembelajaran kewirausahaan pada level pendidikantinggi. Penelitian dilakukan terhadap beberapa perguruan tinggi negeri dan swasta dengan 304 sampel mahasiswa dari beberapa program studibaikuntukbidangeksaktamaupunsosial yang menyelenggarakanmatakuliahkewirausahaan. Dari hasil penelitiandi simpulkan materi pembelajaran kewirausahaan dapat dikelompokkan pada aspek (1) pengetahuan (2) keterampilan dan (3) aspek sikap. Pada masing-masing aspek dikumpulkan materi yang diajarkan dan dikelompokkan serta bagaimana metode pembelajarannya. Hasil penelitian dengan pengujian teknik Anova menunjukkan, terdapat perbedaan beberapa mataeri ajar dan metode belajar dalam fakultas yang sama maupun antar fakultas pada beberapa universitas. Demikian juga dalam konstruksi kognitif terhadap metaphora entreprenurship (keinovasian, kreatif, proaktif dan risk taking) menunjukkan belum diantarkan dengan metode belajar yang relevan, sebagaimana mod(l-model pembelajaran pengembangan personal. Kata kunci :materi ajar, metode belajar, konstruk kewirausahaan